2009
DOI: 10.54207/bsmps1000-2009-07338i
|View full text |Cite
|
Sign up to set email alerts
|

Plant species diversity along an altitudinal gradient in Simbalwara wildlife sanctuary, Himachal Pradesh

Abstract: The composition of forest vegetation along an altitudinal gradient (400 to 650m) in Simbalwara Wildlife Sanctuary was studied during August, 2003. The forest is composed of 53 species of trees, 32 of shrubs and 175 of herbs. The plant communities identified at 400-525m and 525-650m elevation range were Shorea robusta – Mallotus philippensis and Shorea robusta – Terminalia alata respectively. On the basis of importance value index (IVI), Shorea robusta was the dominant tree species at both the elevation ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…The concentration of dominance, diversity index, richness index, and evenness index for shrub was 0.04, 3.71, 8.99 and 0.90 respectively (Table 7). Other supporting pieces of evidence also show similar type of results for biodiversity and phytosocial studies [36][37][38][39][40][41] At an elevation varying from 1000m-1500m, the total number of tree species recorded was 37 (Table 3). Pinus roxburghii was dominant species having the maximum highest value for density ha -1 (110) followed by Punica granatum (56) and Bauhinia variegata (50), and the lowest value (4) was observed for Albizia lebbeck, Albizia julibrissin, Syzygium cuminii and Grewia tiliifolia.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The concentration of dominance, diversity index, richness index, and evenness index for shrub was 0.04, 3.71, 8.99 and 0.90 respectively (Table 7). Other supporting pieces of evidence also show similar type of results for biodiversity and phytosocial studies [36][37][38][39][40][41] At an elevation varying from 1000m-1500m, the total number of tree species recorded was 37 (Table 3). Pinus roxburghii was dominant species having the maximum highest value for density ha -1 (110) followed by Punica granatum (56) and Bauhinia variegata (50), and the lowest value (4) was observed for Albizia lebbeck, Albizia julibrissin, Syzygium cuminii and Grewia tiliifolia.…”
Section: Resultssupporting
confidence: 59%
“…The concentration of dominance (C), diversity index (H), richness index (R), and evenness index (E) for trees was 0.04, 3.58, 7.62, and 0.93, respectively (Table 7). A similar type of flora species has been recorded in the Pine forests of Himachal Pradesh at lower altitudes [33][34][35]18].…”
Section: Resultssupporting
confidence: 52%
“…11) up to 80 and caused 85 percent damage per leaf, and tied 2-6 leaves together in a silken web. Singh and Kaur (2017) also reported 70-80 per cent leaf damage on fig plants caused by P. minor and P. radiata in Punjab from July to September, while, Verma and Dogra (1984) reported it 15-20 per cent damage from Solan (HP).…”
Section: Mode Of Feeding In Early and Late Instar Larvae And Damage T...mentioning
confidence: 97%
“…The decrease in available nitrogen in the deforested area may be due to deforestation, grazing, and tourism which is proportional to the decrease in organic matter and the latter being the bank of soil nitrogen. Verma et al [18] and Zargar et al [19] also reported a significant decrease in available nitrogen in degraded forests, Singh [20] reported medium to high available nitrogen content in forest soils of Kashmir Valley [21, 11, 16 and 13].…”
Section: Assessment Of Biotic Stress On Nutrient Status Of Soilmentioning
confidence: 99%